Multi absorber made from rice husk and CaCl2-KMnO4 in absorbing water vapor and ethylene. Issue 1 (April 2020) - Rahmah, A; Warsiki, E; Iskandar, A
Abstract: The excessive ethylene gas and water vapor are not desired particularly in the fruit post-harvest handling, since the substances can shorten the shelf life and accelerate the rooting of the fruits thus its presence in the fruit handing is needed to be control. In this research, a multi absorber has been manufactured from calcium chloride (CaCl2 ) and potassium permanganate (KMnO4 ) with active rice husk as a matrix. The purpose of this study is to observe the capability of multi absorber of CaCl2 and KMnO4 trapped into rice hush matrix in absorbing water vapor and ethylene. In this study, CaCl2 and KMnO4 solutions with mol ratio of 1 : 2; 2 : 1; 1 : 3 and control (with CaCl2 (1 mol) or KMnO4 (1 mol)) were impregnated into the matrix. The experiment resulted that the ratio of CaCl2 (1 mol): KMnO4 (3mol) was able to absorb KMnO4 as much as 0.89 mg ethylene per 3 g absorber for 1 h of exposure. It also worked for absorbing water vapor as much as 1.03 g/g absorber for 7 days of storage at RH97%. Based on this experiment, the multi absorber resulted from this research is potential to be applied as ethylene and water vapor absorber.